Recent progresses and challenges in smart contact lens - Jiandong XU; Ruisong LI; Hao CHANG; Yi YANG; Sheng ZHANG; Tianling REN (物联网学报)
With advances in the Internet of things, contact lenses not only are limited to vision correction, but also have become an emerging field of the smart wearable device.And with the proposal of the concept of “meta universe”, augmented reality (AR) technology has once again become the mainstream development direction of science and technology.The latest research progress of key technologies of smart contact lenses in physiological signal monitoring, intraocular pressure monitoring, eye-movement tracking, and augmented reality, as well as the energy supply scheme of the contact lenses were summarized comprehensively.And the future development direction of smart contact lenses in intelligent health and augmented reality was looked forward.In the future, smart contact lenses will realize or surpass the functions of smartphone.Their displays can be controlled by eye movement, which enables us to browse various information, such as news, weather, biomarker level, etc.Therefore, the smart contact lens will play an important role in intelligent medical health and meta universe.